Qualıty Assessment Of Routıne Famıly Plannıng Data For Consıderatıon Of Local Polıcy Makıng - Musafaah Musafaah; Tris Eryando; Hadrianti H. D. Lasari (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Research about the unmet need for family planning using routine data has begun to implement. Routine data has advantages, including low cost, comprehensive data available, and data can compare and analyze in time series. The study aims to assess routine data quality related to the unmet family planning needs at the provincial level in Kalimantan, Indonesia. This research is a descriptive internal consistency analysis by looking at achievements over time and consistency between indicators. The quality data is categorized as good if the difference in the ratio isn’t more than 20%. The data assessed is the unmet need for family planning from the publication of the National Population and Family Planning Agency (BKKBN) field control report from 2018-2021. The results showed that the quality of the data assessed from the achievements over time results classified as good in all provinces in Kalimantan. The quality data from the consistency between indicators results classified as good in Central Kalimantan and South Kalimantan in 2018-2021. North Kalimantan has poor data quality throughout 2018-2021. The quality of routine family planning data must continue to be improved so that family planning policy decisions at the local level can to implement adequately